Análise do desempenho térmico de habitações construídas com paredes de blocos de concreto: um estudo de caso em Tucuruí-PA - VASCONCELOS, Dalyla Salazar de (2022)
The present work addresses studies related to the thermal performance of buildings built on walls with concrete blocks and makes an evaluation of this technique in the Vivicidade Housing Complex (CHV), in Tucuruí-PA, in order to verify the compliance with the current rules of the Brazilian Association of Technical Norms (ABNT) ABNT NBR 15575: 2013 and ABNT NBR 15220: 2005 for some criteria according to Bioclimatic Zone 8 (ZB8), in which the studied housing unit is inserted. In addition, a comparative analysis was carried out between the sealing system used in the case study and the concrete wall construction system (sealing system performed in the first phase of the work). For this study, three methods of evaluating thermal performance were adopted: simplified, based on the analysis of the thermal properties of the materials that make up the CHV dwellings; informative, based on the execution of air temperature measurements in the representative housing unit; and normative, with a computer simulation using the EnergyPlus software, together with the support of the SketchUp program for the construction of the three-dimensional model of the building and the OpenStudio plug-in, which integrates the modeling with the energy software. Through the results obtained by the methods used for the evaluation of the thermal performance of the building it was possible to realize which of the construction systems is more suitable to be used in the study region.